Sosiologi Sastra dalam Puisi Hawāmish 'alā Daftar al-Naksah Karya Nizar Qabbani: Refleksi Konflik Palestina-Israel - Aeni, Prisilia Anghuril; Mustari, Mustari (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2024)
This study analyzes the poem Hawāmish 'alā Daftar al-Naksa by Nizar Qabbani through the perspective of Alan Swingewood's sociology of literature. This poem reflects the social, cultural, and political reality of the Palestinian people who are suffering from the prolonged Palestinian-Israeli conflict. The research aims to understand how this poem depicts the trauma of Arab defeat, criticism of the authorities, and hope for future generations. A descriptive qualitative method was used with a focus on content analysis, linking the poem's themes with its socio-historical context. The results show that Qabbani depicts social realities such as economic backwardness, internal conflict, and political repression. The poem also serves as a tool of social criticism that inspires change, especially through a call to the younger generation to fight injustice and build a better future. As such, it is not only a passive reflection of reality, but also a tool of resistance against repressive socio-political conditions. Within the framework of literary sociology, this poem emphasizes the close relationship between the author's social position and the messages contained in his work.